Molecular Mechanisms of TDP-43 Misfolding and Pathology in Amyotrophic Lateral Sclerosis - Prasad, Archana; Bharathi, Vidhya; Sivalingam, Vishwanath; Girdhar, Amandeep; Patel, Basant K. (Frontiers in Molecular Neuroscience, 2019)
TAR DNA binding protein 43 (TDP-43) is a versatile RNA/DNA binding protein involved in RNA-related metabolism. Hyper-phosphorylated and ubiquitinated TDP-43 deposits as inclusion bodies in the brain and spinal cord of the patients with the motor neuron diseases: amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). While majority of the ALS cases (90-95%) are sporadic (sALS), among the familial ALS cases 5-10% involve the inheritance of mutations in the TARDBP gene and the remaining (90-95%) are due to mutations in other genes such as: C9ORF72, SOD1, FUS, and NEK1 etc. Strikingly however, majority of the sporadic ALS patients (up to 97%) also contain the TDP-43 protein deposited in the neuronal inclusions, which suggests of its pivotal role in the ALS pathology. Thus, unravelling the molecular mechanisms of the TDP-43 pathology, seems central to the ALS therapeutics, hence, we comprehensively review the current understanding of the TDP-43’s pathology in ALS. We discuss the roles of TDP-43’s mutations, its cytoplasmic mis-localization and aberrant post-translational modifications in ALS. Also, we evaluate TDP-43’s amyloid-like in vitro aggregation, its physiological versus pathological oligomerization in vivo, liquid-liquid phase separation (LLPS), and potential prion-like propagation propensity of the TDP-43 inclusions. Finally, we describe the various evolving TDP-43-induced toxicity mechanisms such as the impairment of endocytosis and mitotoxicity etc. and also discuss the emerging strategies towards TDP-43 disaggregation and ALS therapeutics.